The identification and management of production-living-ecological space from the perspective of land system science: Connection logic and realization path - JI Zhengxin, XU Yueqing, SUN Danfeng, LUN Fei, SUN Qiangqiang, JIAO Xin, CHEN Lu (Ziyuan Kexue)
The identification and management of production-living-ecological space (PLES) is the core essence of territorial spatial planning and governance in the new era, and a key initiative to achieve regional sustainable development. Currently, research in this field faces practical dilemmas such as the discrepancy between the attribute cognition of PLES and its theoretical construction, the disconnection between the abstract identification of PLES and the refinement of its implementation, and the mismatch between the rigid management of PLES and the dynamic land functions. Land system science can provide a beneficial perspective for conducting research on the detailed identification and dynamic management of PLES. Accordingly, this paper systematically reviews the ideological origin of land system science, elaborates the internal differences and operational structure of the land system, and clarifies the theoretical description and quantitative expression of the land system states. Based on ontological consistency, goal alignment, process relevance, and effect reciprocity, this paper summarizes, this paper summarizes the multi-dimensional interconnected relationship between land system science and the identification and management of PLES, attempts to construct a logical mechanism centered on the land system states between them, sequentially proposes the key solution paths for land system science to support the identification and management of PLES in terms of theoretical foundation, technical channels and practical vision. In the future, it is necessary to conduct typical case practices based on the existing theoretical system to expand the application boundaries of land system science and provide technical methods to solve the problem of PLES coordination in the whole domain.